PARTAI POLITIK DAN KEKUASAAN DI INDONESIA (NILAI BUDAYA DAN KELOMPOK KEPENTINGAN) - Adam, Adam (Hunafa: Jurnal Studia Islamika, 2005)
Political party and power are two interdependent elements. In political party there exist a number of groups of interest. They can influence economical policy of the ruler. Political party and power are also influenced by cultural values. In Indonesia, cultural values which dominate political parties and power are Javanese cultural values.Â Kata Kunci: Partai Politik, Kekuasaan, dan Nilai Budaya